Development of Chemistry Learning Media Based on Instagram Social Media on Material Basic Laws of Chemistry for High School Phase E - Maharani, Windy; Andromeda, Andromeda; Sovia, Eka (Universitas Negeri Padang, 2025)
Field analysis conducted through interviews and questionnaire distribution to students, it is known that there is no learning media using Instagram social media that can be used as an alternative learning media. This research aims to develop learning media based on Instagram social media on the basic chemical law material of phase E of high school, and to produce valid and practical learning media using validity and practicality instruments. The media development model uses the 4-D model. Validation data is analyzed using the Aiken's V formula while the level of practicality is measured by percentage. The results of the study showed that this media is valid with an Aiken's V value of 0.93 and is very practical with a percentage of media practicality by teachers of 97.17% and students of 96.50%. This shows that the learning media developed is valid and practical to be applied in learning.